Molecular detection and identification of relapsing fever Borrelia in ticks and wild small mammals in China. Issue 1 (31st December 2022) - Zhang, Xiao-Ai; Tian, Feng; Li, Yue; Zhang, Xiao-Long; Jiang, Bao-Gui; Liu, Bao-Cheng; Zhang, Jing-Tao; Tian, Shen; Ding, Heng; Li, Shuang; Li, Hao; Fang, Li-Qun; et al.
ABSTRACT: We identified relapsing fever (RF) Borrelia in 1.45% (145/10426) of the ticks and 1.40% (40/2850) of the wild mammals in a field investigation in China. Three RF Borrelia species, including human-pathogenic Borrelia miyamotoi, Borrelia persic a and unclassified Babesia sp. were determined. Main species determined from ticks was B. miyamotoi (44.14%), followed by the unclassified Borrelia sp. (42.76%), and Borrelia theileri (13.10%). In wild mammals, main species found was B. persica (57.50%), followed by the unclassified Borrelia sp. (40.00%), and B. miyamotoi (2.50%). We determined B. theileri and B. persica in China for the first time . The coexistence of RF Borrelia species in one tick species in a given region was observed, with the most frequent coexistence seen for B. miyamotoi and the unclassified Borrelia sp. in Dermacentor silvarum, Haemaphysalis japonica, Haemaphysalis longicornis, and Ixodes persulcatuss respectively. The wide distribution and high variety of RF Borrelia in China pose a potential threat to public health.